The Impact of Indonesia-China Nickel Cooperations on Indonesia’s Economy and Environment - Rosada, Farah; Wibisana, Raden Ambara Arya; Paksi, Arie Kusuma (Faculty of Economics and Social Science, Department of International Relations, Universitas Amikom Yogyakarta, 2023)
As a country with abundant nickel potential, Indonesia possesses numerous advantages that have attracted China to expand its capital in the Indonesia. The collaboration between countries demonstrates the mutual national interests. Following the establishing of downstream policy through Ministerial Regulation No. 11 of 2019, the Indonesian Government has shown increased concern for optimizing its domestic nickel potential. This study examines the impact of cooperation between Indonesia's and China' in the nickel industry on Indonesia's economic growth and environment. It seeks to determine whether this cooperation benefit Indonesian people by fostering advancements in human resources indicators, infrastructure development, and presenting viable solution to environmental challenges through their joint efforts in the nickel industry or vice versa? The research method is qualitative, with critical approaches analyzed using economic diplomacy theory. The results shows that this cooperation positively impacts Indonesia's economic growth, especially in terms of increased employment, human resource development, and infrastructure development. However, it also presents new challenges on environmental issues. Indonesia's endeavors to address environmental problems stemming from the nickel industry involve pressuring China, as an investor, to uphold environmental standards within the mining areas.